تأثير العاب تنافسية حركية في تطوير كفاءة الأداء الفني لبعض المهارات في الكرة الطائرة للطالبات - الجليل, أفراح باقر عبد (Sulaimani Journal for Humanities, 2018)
Summary The significance of current research in an attempt to develop a set kinetic games competitive contribute to the development of the technical performance of some skills in volleyball for the students efficiency and help existing educational process in the faculties and departments of physical education and sport sciences in various tasks move or educational duties and connected to their students so that they can acquire various patterns locomotor behavior, unwanted and mastery, which may help them to interact positively and to respond to the requirements of the special skills to be learned. The research aims to: 1. Prepare competitive games. 2. Establish an equation to measure the technical performance of some skills in volleyball for the students efficiently. 3. identify the impact of competitive gaming motor in the development of the technical performance of some skills in volleyball for the students efficiently. Researcher experimental method used in line with the nature of the problem was identified research community by students the second stage in the faculties of Physical Education and Sports Science at the University of Kufa, totaling 14 students, were divided on the experimental groups and the control group randomly (in a manner of lots) for the purpose of application of the curriculum, by (7) students each group then was conducted harmonies to them before embarking on the curriculum of education of competitive games motor and then was conducting the pre-test, then it was conducted parity in the technical performance of some skills in volleyball efficiency and later was presented the curriculum by (12) a week, and then was posttest and get the results that were processed using a statistical procedure bag (SPSS).